EFEKTIFITAS PENGELOLAAN DANA SIMPAN PINJAM KELOMPOK KHUSUS PEREMPUAN (SPP) PADA UNIT PENGELOLAAN KEGIATAN PNPM DI KECAMATAN BUNTULIA KABUPATEN POHUWATO TAHUN 2011-2013 - Muhammad Anas (AkMen JURNAL ILMIAH, 2015)
This study aimed to describe the effectiveness of the management of funds Savings and Loan Special group Women (SPP) in units of PNPM Event Management In District Buntulia Pohuwato 2011-2013. The benefits of this research is to provide information about the effectiveness of the activities undertaken members of Savings and Loans Special Women in District Buntulia Pohuwato and provide information to those who need the information. Data collecting primary data and secondary data. Primary data obtained by distributing questionnaires to the respondents, while secondary data obtained from the institutions associated with the research. The method of sampling is done by "cluster sampling". Respondents were chosen was a member of the women's savings groups. Total sample of 30 members of the women's savings groups. Based on the results of the study, showed that the effectiveness of women's savings groups in the District Kauditan relatively effective with a percentage of 93%. This means that all members of the group use the funds for productive activities by adding capital to businesses that they run in order to further develop the business.